Granice i pogranicza - próba konceptualizacji w warunkach procesów globalizacji = Borders and borderlines - an attempt of conceptualization in global processes conditions - Marczewska-Rytko, Maria (1962- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The issues connected with borders and borderlines are gaining a new dimension in global processes conditions. The objective of this article is to demonstrate the new criteria of the recognition of boarders. The notions of a border and a borderline are ambiguous and they are presented in many different ways by various disciplines. We most often point out the social, cultural and territorial dimension of boarders.
Keywords: granice; pogranicze; globalizacja